FROM OPTIMISM TO DISAPPOINTMENT: THE EVOLUTION OF SWAMI VIVEKANANDA’S ATTITUDE TOWARDS THE WEST - E. V. Volgina (Vestnik MGIMO-Universiteta)
This article belongs to the body of imageological studies dealing with mutual perceptions of nations, communities and cultures as well as the idea of “Other”. The main topic is the evolution of attitude to the West in the works of Swami Vivekananda, who was a social and religious figure on the cusp of XIX – XX centuries and an ideologist of Indian nationalism. It is widely known that roots of the actual social and political thought in India go back to the period of colonialism. With the status of one of the most influential thinkers in modern India and attention paid to the legacy of Vivekananda by ruling Bharatiya Janata Party and Prime Minister Narendra Modi, his case appears to be of a considerable importance. Vivekananda spent years in America and Europe, establishing contacts and promoting Indian culture. He used it as a “soft power” to draw attention of the West to the national liberation struggle just starting to unfold in India. So the research goal is to trace the transformation of Swami Vivekananda’s attitude to the West and find out how its picture after the author’s close acquaintance with Western countries is different from the one in his earlier works. In this context the research focuses on his travel writings created while in the West as well as back in India. In addition to a number of traditional means of research, i.e. historical genitival and historical comparative, content analysis and discourse analysis are also employed. The result of the research says for a rather significant devaluation of the West in Swami Vivekananda’s eyes. His views develop from an enthusiastic, optimistic expectation of Western help in the struggle against British colonialism to the realization that the declining West, torn by interstate differences on the verge of a great war, is not willing to provide an active support to the Indian people, notwithstanding its interest to the Indian civilization. So his last works present evident criticisms of the West and appreciation of India as the source of moral integrity, which the West is devoid of and which is vital for a further development of the mankind.